2002
DOI: 10.1080/10810730290088094
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Medical Information Seeking Among African American Cancer Patients

Abstract: Qualitative research methods were used to explore factors that may affect medical information seeking, treatment engagement, and emotional adjustment among African American cancer patients. Focus group findings suggest that an array of cultural and socioeconomic factors plays important roles in the behavior of African American cancer patients. Participants described a number of important barriers and facilitators of medical information seeking and treatment participation. Factors linked to the health care-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
144
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(152 citation statements)
references
References 18 publications
7
144
0
1
Order By: Relevance
“…For example, a qualitative, focus-group study among persons who had received treatment for ischemic heart disease in two urban, university hospitals (Ferguson et al, 1998) found that African Americans were particularly likely to mention perceived discrimination, perceptions of the patient-physician relationship, and spiritual issues as factors that influenced decision making regarding cardiac care. A second study of African-American cancer patients, found that mistrust of the medical community, concerns about privacy, and perceived stigma concerning seeking help for emotional support were cited as barriers in seeking treatment for cancer among African Americans (Matthews, Sellergren, Manfredi, & Williams, 2010). While these studies give important insight into medical decision making among African Americans, very little information is available concerning hospital decision making from the perspective of these patients and their caregivers (Torke, Corbie-Smith, & Branch, 2004).…”
Section: Decision Making and African Americansmentioning
confidence: 99%
“…For example, a qualitative, focus-group study among persons who had received treatment for ischemic heart disease in two urban, university hospitals (Ferguson et al, 1998) found that African Americans were particularly likely to mention perceived discrimination, perceptions of the patient-physician relationship, and spiritual issues as factors that influenced decision making regarding cardiac care. A second study of African-American cancer patients, found that mistrust of the medical community, concerns about privacy, and perceived stigma concerning seeking help for emotional support were cited as barriers in seeking treatment for cancer among African Americans (Matthews, Sellergren, Manfredi, & Williams, 2010). While these studies give important insight into medical decision making among African Americans, very little information is available concerning hospital decision making from the perspective of these patients and their caregivers (Torke, Corbie-Smith, & Branch, 2004).…”
Section: Decision Making and African Americansmentioning
confidence: 99%
“…However, not all survivors want that much information. The amount and timing of information desired varied in those with a blunting style (avoiding threatening information) or for those trying to maintain hope [5,11,12,18,[20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…No ready explanation for this observation is provided by demographic differences (such as age, gender, education, or income) between our study population and those previous studies. Although the professional literature related to health care in the United States is replete with articles that refer to the impact and assumed legacy of the Tuskegee Syphilis Study, [1][2][3]6,[13][14][15][16][17][18][19][20][21][22][23][24][28][29][30] perhaps the most unusual measure of the depth of cultural influence of this legacy is documented by its recent appearance as the core theme of a Marvel comic book 7-issue series: "Truth: Red, White and Black," written in 2003 as a presequel to the Captain America series. In this fictional presequel series, research abuses abound in experiments done on a Black military unit.…”
mentioning
confidence: 99%
“…Although a considerable amount has been written about the long-lasting effects of the Tuskegee Syphilis Study on the Black community, most of this work has been from a legal, historical, ethical, or access to health care perspective. [8][9][10][11][12][13][14][15][16][17][18][19][20] Surprisingly few research articles have directly examined whether any differential participation of Blacks or other minorities in biomedical studies compared with participation of Whites was because of the legacy of the Tuskegee Syphilis Study or because of other factors. [21][22][23][24][25][26][27][28] A recent literature review noted that only 5 of the published studies to date have presented quantified data that compared Black with White participation and the relation to the Tuskegee Syphilis Study, 29 and most of them only used a single question on willingness to participate as their measure of this complex decison.…”
mentioning
confidence: 99%